Surgical treatment of partial atrioventricular septal defect: functional analysis of the mitral valve in the postoperative period - Castro Neto,Josué Viana (2002)
OBJECTIVE: To study mitral valve function in the postoperative period after correction of the partial form of atrioventricular septal defect. METHODS: Fifty patients underwent surgical correction of the partial form of atrioventricular septal defect. Their mean age was 11.8 years and 62% of the patients were males. Preoperative echocardiography showed moderate and severe mitral insufficiency in 44% of the patients. The mitral valve cleft was sutured in 45 (90%) patients (group II - GII). Echocardiographies were performed in the early postoperative period, and 6 and 12 months after hospital discharge. RESULTS: The patients who had some type of arrhythmia in the postoperative period had ostium primum atrial septal defect of a larger size (2.74 x 2.08 cm). All 5 patients in group I (GI), who did not undergo closure of the cleft, had a competent mitral valve or mild mitral insufficiency in the preoperative period. One of these patients began to have moderate mitral insufficiency in the postoperative period. On the other hand, in GII, 88.8% and 82.2% of the patients had competent mitral valve or mild mitral insufficiency in the early and late postoperative periods, respectively. CONCLUSION: The mitral valve cleft was repaired in 90% of cases. Echocardiography revealed competent mitral valve or mild mitral insufficiency in 88.8% and 82.2% of GII patients in the early and late postoperative periods, respectively.